2006
DOI: 10.1016/j.physa.2006.04.113
|View full text |Cite
|
Sign up to set email alerts
|

Hidden forces and fluctuations from moving averages: A test study

Abstract: The possibility that price dynamics is affected by its distance from a moving average has been recently introduced as new statistical tool. The purpose is to identify the tendency of the price dynamics to be attractive or repulsive with respect to its own moving average. We consider a number of tests for various models which clarify the advantages and limitations of this new approach. The analysis leads to the identification of an effective potential with respect to the moving average. Its specific implementat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…The factor M − 1 in the denominator of the force term makes the potential independent of the particular choice of the moving average [17]. This equation has been used in previous papers to analyze real data [17,19,20]. The conclusion is that is indeed possible to observe this kind of forces also in real stock-prices.…”
Section: Definition Of a Minimal Abm With Fundamentalists And Chartistsmentioning
confidence: 95%
See 1 more Smart Citation
“…The factor M − 1 in the denominator of the force term makes the potential independent of the particular choice of the moving average [17]. This equation has been used in previous papers to analyze real data [17,19,20]. The conclusion is that is indeed possible to observe this kind of forces also in real stock-prices.…”
Section: Definition Of a Minimal Abm With Fundamentalists And Chartistsmentioning
confidence: 95%
“…In our model we can overcome this complication by simplifying the chartists' behavior. In fact, the description of chartists is in term of the recently introduced potential method [17,18,19,20]. Chartist agents detect a trend by looking at the distance between the price and its smoothed profile which in our case is the moving average computed on the previous M time steps.…”
Section: Definition Of a Minimal Abm With Fundamentalists And Chartistsmentioning
confidence: 99%
“…Note that previous studies have shown that several features of empirical market dynamics are determined by an effective potential defined in terms of the long-term moving average of price [22]. Given the price information, an agent i decides to trade at time t according to the probability…”
mentioning
confidence: 99%
“…In recent papers [3,4] has been introduced the idea the the stock-price dynamics can be influenced by a moving average of the price itself in the previous time steps. Hence, at every time step t, one can introduce a moving average of the previous M time steps: average defined as the average over the previous 50 points.…”
Section: The Effective Potential Modelmentioning
confidence: 99%